ANALISA UJI KEKUATAN MATERIAL TROLI PADA SEPEDA BERBAHAN BAJA KARBON RENDAH - Rama Irdyan Rama Irdyan; Subkhan Subkhan; Rodika Rodika (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Trolley is a means of moving from one area to another. A very helpful manual tool for moving goods, in order to facilitate the movement of an item to the destination. However, these activities will be hampered if the luggage is a lot and heavy. So the trolley will be made slightly different from the general trolley, namely in the form of a trolley that can be paired as a bicycle holder. This tool has a main frame that can be called for a load, the frame itself uses low carbon steel material in the form of a hollow box, namely St37 steel with a length of 188 mm, width 15x15 mm and thickness of 1.3 mm. In this study, to complete the analysis of frame strength using Solidworks Software, using a static simulation feature so that the stress value that occurs can be known. Solidworks is able to improve and validate performance and reduce the need for prototypes or costly design changes at a later date. The results of this study indicate that the trolley using low carbon steel material with a predetermined size is able to withstand the load of 30 kg.